Are phosphodiesterase inhibitors effective and safe for men with diabetes and erectile dysfunction?. Issue 2 (February 2018) - Bayerman, Boris; Glass, Gina G.; Aggarwal, Aarti
Abstract : EVIDENCE‐BASED ANSWER : Yes. As‐needed use of sildenafil, tadalafil, and vardenafil lead to large improvements in erectile function in men with diabetes. Tadalafil taken daily results in nearly 20% more men able to complete intercourse, but only marginal clinical benefit in overall erectile function compared with placebo. Adverse events occur up to twice as often with phosphodiesterase type 5 (PDE‐5) inhibitors than placebo, but are minor such as headache and dyspepsia (SOR: A, meta‐analyses of RCTs). Vardenafil taken daily improves global erectile function scores, with mean scores at the level considered to be normal erectile function (SOR: B, single RCT).